Care participation and burden among informal caregivers of older adults with care needs and associations with dementia. (19th October 2015) - Vaingankar, Janhavi Ajit; Chong, Siow Ann; Abdin, Edimansyah; Picco, Louisa; Jeyagurunathan, Anitha; Zhang, YunJue; Sambasivam, Rajeswari; Chua, Boon Yiang; Ng, Li Ling; Prince, Martin; Subramaniam, Mythily
ABSTRACT: Background: Few studies have estimated care burden in large, representative, multi-ethnic Asian population-based informal caregivers of older adults with care needs. This study describes informal caregivers' care participation for a population-based sample of older adults with care needs in Singapore, investigates differences by dementia status, and examines correlates of caregivers' burden. Methods: Data collected from 693 pairs of older adults, aged 60 to 100 years, having any care needs, and their informal caregivers, who were aged 21 to 88 years, closely involved in their care and "knew the older resident best, " and were interviewed during a cross-sectional national survey, were used. Clinical characteristics of older adults, including behavioral and psychological symptoms of dementia (BPSD) and dementia diagnosis, care needs, and socio-demographic characteristics of participants were obtained. Care burden was assessed with the Zarit Burden Interview. Results: Informal caregivers' participation was highest in activities related to communication (35.1%), feeding (32%), and bathing (21.1%). Among the older adults with any care need, 356 (51.4%) had dementia. Care burden was significantly associated with married caregivers (odds ratio (OR) 2.4 vs. never married), when their relative belonged to a younger cohort (OR 2.5 vs. >84 years), needed care much of the time (OR 2.5 vs. no care needed), exhibited BPSD (OR 3.5 vs. no BPSD), and had dementia (OR 2.52 vs. no dementia). Conclusions: Factors related to older adults – more care needs, presence of BPSD, and dementia – were significant contributors to informal caregivers' burden, and these should be considered while planning interventions to alleviate care burden.